Critical Lexicography at Work: Reflections and Proposals for Eliminating Gender Bias in General Dictionaries of Spanish - Fuertes-Olivera, Pedro A.; Tarp, Sven (Lexikos, 2022)
This study highlights the fact that dictionaries are ideological texts that are very influential, because millions of people regard them as sources of authority. It shows that existing general dictionaries of Spanish are so gender-biased that they contribute to the upholding of unfair situations, for example, by making women invisible and maintaining gendered traditions based on male-centred power and ideology. In order to avoid such an unfair situation, we introduce several new ideas regarding the question of language and gender. We also show how this can be put into practice in a dictionary portal that we are constructing at the time of writing this article. Therefore, this article offers several specific solutions with the aim of making women lexicographically visible, promoting the use of inclusive language in public and private discourse and eliminating gendered practices.Keywords: inclusive language, dictionary, Spanish, ideology, profession nouns